Power Efficient Clock Distribuition for Switched Capacitor DC-DC Converters - A. S. R. Murthy; Sridhar T. (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In various VLSI based digital systems, on-chip interconnects have become the system bottleneck in state-of-the-art chips, limiting the performance of high-speed clock distributions and data communication devices in terms of propagation delay and power consumption. Increasing power requirements and power distribution to multi-core architectures is also posing a challenge to power distribution networks in the integrated circuits. Clock distribution networks for the switched capacitor converters becomes a non-trivial task and the increased interconnect lengths cause clock degradation and power dissipation. Therefore, this paper introduce low swing signaling schemes to decrease delay and power consumption. A comparative study presented of low voltage signaling schemes in terms of delay, power consumption and power delay product. Here, we have presented a power efficient signaling topology for driving the clocks to higher interconnect lengths.